Remote area power supply through suitable solar PV augmented micro‐hydro generation: A case study. (13th November 2019) - Parida, Adikanda; Chatterjee, Debashis
Summary: Electrification in remote villages using locally available hybrid renewable energy sources is a viable option to eradicate energy poverty. At the same time, energy supply to the unprivileged population at the affordable cost is a major issue. Moreover, appropriate technology is the key factor for the sustainable operation of small‐scale generation system in remote places. Therefore, in this paper, a simple controller‐based standalone solar photovoltaic (PV) augmented micro‐hydro generation system suitable for remote area has been proposed. Because of its robustness for wide speed range applications, doubly fed induction generator (DFIG) has been used for micro‐hydro power generation in the proposed scheme. The developed controller effectively stabilizes the load voltage with load, micro‐hydro generation, and solar PV generation variations. In order to provide cost‐effective renewable power supply to the rural population, a generation capacity trade‐off criterion has been developed considering solar PV and micro‐hydro generations as the two operators. In the proposed trade‐off process, cost analysis has been performed considering the salvage dumping cost (SDC) for solar PV. The proposed hybrid generation scheme has been simulated through HOMER Pro‐3.2 for cost‐benefit analysis. Also, a prototype hardware set‐up for the proposed scheme has been developed and tested successfully. In this paper, Section 1 describes literature review; Section 2 discusses power generation strategy; Section 3 discusses energy cost analysis; and Section 4 describes experimental results.